THE PERFORMANCE EVALUATION OF R744 TRANSCRITICAL EJECTOR AND R290/R744 CASCADE REFRIGERATION SYSTEMS FOR TURKEY - (:unkn) unknown (VINCA INST NUCLEAR SCI, 2019)
In this study, performance of two different environmentally friendly systems with natural refrigerant solutions, R744 transcritical booster system with ejector and a R290/R744 cascade system are examined theoretically by using engineering equation solver software. Operating conditions are determined to represent different climatic regions in Turkey using summer dry bulb temperatures of various cities. The transcritical and the cascade system are assumed to operate at two different evaporation temperatures of -10 degrees C and -32 degrees C. The overall energy efficiency ratio values for each system with respect to the same ambient and evaporation conditions are compared and evaluated. Finally, performance of both systems has been compared and the appropriate solution for each city has been suggested. For cold and mild climate regions of Turkey, the performance of transcritical alternative is found better than the proposed cascade system. Moreover, the performance of transcritical system is observed slightly lower than those of the cascade system in hot climate regions of Turkey such as Aegean, Mediterranean, and South-East Anatolian regions. It is also found that the performance of the transcritical system is better in regions having lower ambient conditions such as near the Black Sea and eastern regions of Turkey. Therefore, for the mild and cold regions of Turkey, the transcritical ejector option is the better alternative due to having higher performance compared to the cascade system.
Keywords: natural refrigerants; transcritical ejector system; cascade system; energy efficiency ratio; INTERNAL HEAT-EXCHANGER; THEORETICAL EVALUATION; CO2; ENERGY; CYCLE